Effects of X-Ray Radiation on Atomic Structure: A Physical Review Based on Literature Studies - Lumbantoruan, Sri Rezeki; Silalahi, Renata Agustina; Khairunnisa, Adinda Dwi; Khairani, Farizka; Silalahi, Jihan Syifa; Rivaldo, Samuel; Jubaidah, Jubaidah; Rugaya, Rugaya (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Purpose This research aims to explore the effects of X-ray radiation on atomic structure from a physics perspective, with an emphasis on how the interactions take place, their effects on electron configurations, and the physical consequences that arise. This review aims to communicate a deeper understanding of how X-ray radiation changes atomic dynamics and the underlying mechanisms, by combining the results of recent research. Design/Methods/Approach The research approach uses a systematic literature review methodology, which involves the identification, selection, and analysis of relevant academic materials. The sources examined include theoretical and experimental studies related to X-ray interaction mechanisms, such as photoelectric phenomena, Compton scattering, and pair production. This approach allows for a critical analysis of previous results and the integration of data to provide a comprehensive understanding of the physical effects of X-ray radiation on atomic structure. Findings TThe findings of this review indicate that X-ray radiation can cause ionization of atoms, excitation of electrons, and also changes in subatomic particles at high energy levels. The photoelectric effect serves as the main mechanism affecting the arrangement of electrons in atomic shells, while Compton scattering shows the change in photon energy due to interaction with free electrons. Pair production is observed at very high X-ray energy levels, indicating the conversion of radiation energy into new particles. Research Implications/Limitations The implications of this study include enriching the understanding of radiation physics and developing technologies that use X-ray radiation for scientific and industrial purposes. However, there are limitations to this study, namely the lack of direct experimental evidence to support certain literature analyses. Additional research is needed to deepen the understanding of the complex interactions between X-ray radiation and atomic structures, especially under extreme conditions.